New inversion formulae for PIDF controllers with complex zeros for DC-DC buck converter - Cuoghi, S.; Ntogramatzidis, Lorenzo (2016)
© 2016 IEEE.This paper presents a new tracking controller design method for the widely used DC-DC buck converter involving a PIDF (i.e., PID + filter) controller. This controller, differently from the classical PID controller, has the advantage of being characterized by a proper transfer function. Secondly, the further degree of freedom introduced in the transfer function of the low pass filter can be exploited to satisfy further specifications. This new design procedure is a conjunction of the classical pole-zero cancellation method with the so-called inversion formulae design method. These two techniques are used to reduce the negative effects introduced by the complex poles in the transfer function of the converter and to exactly satisfy steady state requirements on the tracking error, as well as to meet frequency-domain specifications on the phase margin and on the gain crossover frequency. The robustness of the proposed control procedure under load variations and plant uncertainty is evaluated and compared with other methods.